Financial Performance Developments Towards Sustainability of Developing Countries in ASEAN - Sari, Rafika; Syafitri, Lili; Puspita Sari, Ranti (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
This study investigates the progress of financial performance and its consequences for the desires of developing countries in the ASEAN region. This study examines the complex relationship between financial indicators and desire outcomes, with the aim of gaining an understanding of the factors that influence and hinder the achievement of desire goals. This research uses an integrated approach that combines quantitative analysis with qualitative knowledge, using a mixed methods approach. Quantitative analysis uses regression analysis to test hypothesized relationships, while qualitative analysis uses thematic analysis to identify ethical considerations. This enhances their standing and fosters trust among stakeholders, ultimately contributing to organizational survival and stakeholder engagement as well as supporting the company's efforts to achieve a balance between profitability and social responsibility. Thus, it is hoped that this research can provide an important contribution to the literature discussing the relationship between financial performance and extinction in the ASEAN region, as well as providing practical recommendations for policy makers and industry players in improving their curiosity strategies. This research is also expected to provide a foundation for future research to explore other mechanisms that contribute to organizational desirability in developing countries. as well as providing new insights into how organizations in developing countries can leverage their resources strategically to create long-term value for stakeholders. By understanding the factors inhibiting and triggering disasters, this research also contributes to formulating more effective policies to support inclusive and sustainable economic transformation. Keywords: Financial Performance, Sustainability Development, ASEAN